Bio-based solvents as entrainers for extractive distillation in aromatic/aliphatic and olefin/paraffin separation - Brouwer, Thomas; Schuur, Boelo (Green chemistry : an international journal and green chemistry resource : GC, 2020)
The use of a wide range of bio-based solvents as entrainers in extractive distillation applications was investigated. The separation of hydrocarbon mixtures containing aromatic and aliphatic compounds is highly relevant, and the use of bio-based solvents for this separation was studied using the model system of methylcyclohexane and toluene. Additionally, the use of bio-based solvents for the difficult olefin/paraffin separation was studied using the model system of n -heptane and 1-heptene. From all of the bio-based solvents studied, Cyrene™ showed the highest relative volatility in the methylcyclohexane-toluene system. At compositions up to 40 wt% of methylcyclohexane in the hydrocarbon mixture, with a relative volatility of 3.17 ± 0.16 at 1000 mbar, the selectivity was comparable with the state-of-the-art industrial solvent Sulfolane™. At higher methylcyclohexane fractions, Cyrene™ outperforms Sulfolane™, resulting in a 43% reduction of the minimum reflux ratio, which is an excellent measure of energy efficiency. With regard to the relative volatility of n -heptane over 1-heptene, Cyrene™ also induces an increase in the relative volatility, but not as much as the industrial benchmark n -methylpyrrolidone (NMP). A relative volatility of 1.20 was measured at a solvent-to-feed ratio of 3 (mass basis), which can be further increased by the addition of extra Cyrene™. This leads to the prospect that Cyrene™ may be used for extractive distillation in olefin/paraffin separations, replacing NMP which is subject to severe environmental restrictions by the REACH agreement due to toxicity. A series of bio-based solvents were studied for application as entrainers in extractive distillation with Cyrene™, and compared to sulfolane, 30% energy saving was found for methylcyclohexene distillation from toluene.